2018
DOI: 10.1097/pts.0000000000000522
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Patient Safety Culture in Palestinian Public Hospitals: Impact of Quality and Patient Safety Initiatives and Programs

Abstract: Compared with the baseline survey results, patients' safety initiatives and quality improvement programs had positive effect on the safety culture in public Palestinian hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…According to a study by Hamdan et al in a Palestinian public hospital, patient safety initiatives and quality improvement programs were effective in fostering patient safety culture. [ 27 ] It is well recognized that patient safety training and education can improve patient safety attitudes and patient outcomes. [ 18 ] In our hospital, various patient safety initiatives have been ongoing for more than a decade under the leadership of the medical safety management department, such as patient safety slogan competitions in which patients participate, patient safety training camps, in-hospital patient safety workshops, and efforts to improve underreporting of incidents.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Hamdan et al in a Palestinian public hospital, patient safety initiatives and quality improvement programs were effective in fostering patient safety culture. [ 27 ] It is well recognized that patient safety training and education can improve patient safety attitudes and patient outcomes. [ 18 ] In our hospital, various patient safety initiatives have been ongoing for more than a decade under the leadership of the medical safety management department, such as patient safety slogan competitions in which patients participate, patient safety training camps, in-hospital patient safety workshops, and efforts to improve underreporting of incidents.…”
Section: Discussionmentioning
confidence: 99%
“…Patient safety is an international health concern affecting patients in various health care settings, patient safety as a health care discipline has emerged as a major concern due to the complexity of health care systems and the increase in unsafe care delivered to patients in various health services institutions [ 1 , 2 ]. Patient safety is defined as “a framework of organized activities that creates cultures, processes, procedures, behaviors, technologies, and environments in health care that consistently and sustainably lower risks, reduce the occurrence of avoidable harm, make the error less likely and reduce its impact when it does occur” [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Essential components of safety culture are the attitudes of doctors to medical error, such as disclosure of error, responsibility for error, and it has been suggested that this can be improved by appropriate education in postgraduate training and medical schools [6,7]. In Palestine, which consists of two geographically separate parts, the West Bank and the Gaza Strip, major efforts have been made in the West Bank to improve patient safety in local hospitals with the patient friendly initiative and partners such as the WHO [13][14][15]. However, only a limited effect could be shown on patient safety attitudes, even after major investment in this effort with the greatest improvement of only 9.4% having been shown in the area of incidence reporting [13].…”
Section: Introductionmentioning
confidence: 99%